The Fifth International Symposium of the History of Arab Science: El Carmen de los Martires Granada, Spain Ramadan 26-Shawwal 1, 1412/March 30-April 4, 1992 (American Journal of Islam and Society, 1992)
In the context of the five-hundred-year anniversary celebrations of the"discovery of the New World" now going on in the United States andSpain, the Syrian Institute for the History of Science (Aleppo University,Aleppo, Syria), organized the Fifth International Symposium of the Historyof Arab Science in conjunction with the lnstituto de Cooperaci6n conel Mundo Arabe (Institute of Cooperation with the Arab World, the ForeignMinistry of Spain). The theme of the conference, which dealt withthe contribution of al Andalus (i.e., Muslim Spain) to the history ofscience and teclmology, was the obvious reason for this international cooperationbetween the agencies of Syria and Spain.The contribution of al Andalus in the realms of science and technologyto both Muslim and European countries is undeniably importantin its own right and should be investigated by similar symposia, not onlyin Spain or Muslim countries. It was, however, ironic that the fivehundred-year anniversary celebrations of the "discovery of the NewWorld" coincided with the expulsion of Muslims from Spain after the reconquista,not to mention the fact that the "New World" had already beendiscovered thousands of years before Columbus by the native Americans ...